Evaluasi Penggunaan Asap Cair Tempurung Kelapa pada Konsentrasi dan Daya Simpan Ikan Segar - Juniarti Nomleni , Endang Marlen ; Tolan , Blacius ; Abrina Anggraini , Sinar Perbawani ; Yuniningsih , Susy (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Fish is one source of  food that contains lots of protein. In fish other than containing high protein also contains water which is high enough so that fish easily rot. There fore, it is necessary to take care to over come decay in order to maintain the quality of fish and extend the shelf life of fish without reducing the nutritional value oef fish. This handling can be done by giving liquid smoke where liquid smoke acts as an anti-microbial so that it can inhibit bacterial growth. The purpose of this research  is to fing out the use of liquid smoke as a natural preservative in fresh fish. The raw material used in this research is the coconut shell using the main tool of the pyrolysis reactor. Research  also used an experimental method with a variabel of 0-48 hours and concentration 0%, 2%, 4%, 6% and 8%. Analysis using GC-MS with measured parameters is phenol, benzopirin levels, pH value and yield. The result of the research conducted the concentration of liquid smoke and optimum storage time when applied to fresh fish is the concentration of liquid smoke 2% with a storage time of 12 hours and a concentration of 4% with a storage time of 12 with phenol level of 5,78% and pH value 1,42.